2022
DOI: 10.14704/nq.2022.20.3.nq22054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Number of Pulses on Characterization of Nanoparticles of Copper and its Oxides Synthesized by Nd: YAG Laser Ablation Technique and its Antibacterial Activity

Abstract: Pulsed laser ablation in liquid (PLAL) technique can produce high purity nanoparticles, it is a top-down physical method based on the principle of dividing metal ion bulk precursors into metal atoms, this method is used in this work to synthesis copper nanoparticals (CuPNs) by use Nd: YAG laser with two wavelengths (355 nm) and (532 nm) at energies (500 mJ) and (600 mJ) respectively, with number of pulses (700, 800, 900, 1000, and 1100 P) for each wavelength. The properties of the prepared nanoparticles were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The absorption spectrum of materials is one of the main indicators of the formation of nanoparticles, as the absorption spectrum of nanoparticles differs from that in the case of bulk materials, as it is characterized by the appearance of a peak representing the surface plasmon resonance (SPR), which is a distinctive characteristic of every nanomaterial in its absorption spectrum, as it is responsible for changing the color of the nano solution [10]. Figure (4) shows the absorbance spectra of the prepared colloidal solution and it is found that the SPR is about (300 nm) which agrees with previous studies [1, 12, and 14].…”
Section: Uv-vis Spectrophotometer Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption spectrum of materials is one of the main indicators of the formation of nanoparticles, as the absorption spectrum of nanoparticles differs from that in the case of bulk materials, as it is characterized by the appearance of a peak representing the surface plasmon resonance (SPR), which is a distinctive characteristic of every nanomaterial in its absorption spectrum, as it is responsible for changing the color of the nano solution [10]. Figure (4) shows the absorbance spectra of the prepared colloidal solution and it is found that the SPR is about (300 nm) which agrees with previous studies [1, 12, and 14].…”
Section: Uv-vis Spectrophotometer Analysismentioning
confidence: 99%
“…All science fields are implicated in nanotechnology, including materials science, physics, chemistry, biology, engineering, and computer science, where nanotechnology is a modern specialization of research [1][2][3][4][5]. Nanoparticles (NPs) have a large surface area, magnetic, and mechanical properties, better surface-to-volume ratios, as well as outstanding chemical stability in high temperatures and severe environments [6][7][8][9][10]. NPs can be fabricated from different materials and can be synthesized using various techniques that are based on biological, chemical, or physical [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%